2019
DOI: 10.4025/jphyseduc.v30i13039
|View full text |Cite
|
Sign up to set email alerts
|

Âmbitos de atuação profissional de egressos dos cursos de pós-graduação em educação física da UFSC

Abstract: O estudo objetivou analisar os cenários antecedente e atual de atuação profissional de egressos dos cursos de mestrado e de doutorado em Educação Física, da Universidade Federal de Santa Catarina, entre 2006 e 2013. No estudo descritivo, de fonte documental, foram consultados os currículos (Plataforma Lattes) de um total de 276 ingressantes. Antes de ingressarem no mestrado e no doutorado, a atuação profissional dos egressos concentrava-se nos ambientes não formais, ensino superior público e educação básica. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 13 publications
(20 reference statements)
0
7
0
Order By: Relevance
“…After completing the course, the highest admission was in public institutions, as observed in the Physical Education program of University of São Paulo (USP), with 65% of graduates enrolled in public IHE 15 . Fact was similarly evidenced by Milan et al 12 when analyzing the antecedent and current scenarios of professional intervention of graduates of the master's and doctoral courses in Physical Education of the Federal University of Santa Catarina in the period of 2006 to 2013. Few are those that act autonomously, without links which seems to reflect in the programs recommended in the National Postgraduate Plan 2011-2020 as a goal for the labor market 2,3 .…”
Section: Discutionmentioning
confidence: 76%
See 4 more Smart Citations
“…After completing the course, the highest admission was in public institutions, as observed in the Physical Education program of University of São Paulo (USP), with 65% of graduates enrolled in public IHE 15 . Fact was similarly evidenced by Milan et al 12 when analyzing the antecedent and current scenarios of professional intervention of graduates of the master's and doctoral courses in Physical Education of the Federal University of Santa Catarina in the period of 2006 to 2013. Few are those that act autonomously, without links which seems to reflect in the programs recommended in the National Postgraduate Plan 2011-2020 as a goal for the labor market 2,3 .…”
Section: Discutionmentioning
confidence: 76%
“…The postgraduate scenario in physical education showed that continuing education in postdoctoral stages has been a demand for a reduced number of graduates, as evidenced in other programs in Brazil 15 . However, most of them engage in teaching career before they finish the course, which may facilitate their subsequent insertion in the job market due the opportunities presented to the students during the course period 12 .…”
Section: Discutionmentioning
confidence: 99%
See 3 more Smart Citations